Directrices para la implementación de un modelo de gestión de la relación con el cliente en el sector industrial: caso DAMERA - Wakabayashi, José Luis (2015)
In this research, the case method is applied to analyze the implementation of a Customer Relations-hip Management model in an industrial company. To this end, the Peppers and Rogers’s proposal wasused and integrated with the characteristics of the specific type of demand used in the industrial sector.A diagnosis was developed in order to evaluate the potential of the company to implement the model,and a matrix of customer classifications was developed. Finally, a survey was implemented for identifyingcustomer segmentation variables and contact points, thereby defining value groups for the company.